Sulphapyridine–a new agent for the treatment of ocular cicatricial pemphigoid. Issue 6 (June 1996) - Elder, M. J.; Leonard, J.; Dart, J. K.
Abstract : AIMS–Ocular cicatricial pemphigoid (OCP) is a severe, potentially sight threatening systemic disease that sometimes requires systemic immunosuppression. This study assessed the clinical outcome of patients with OCP treated with sulphapyridine, a sulphonamide with an anti-inflammatory and immunosuppressive action but few side effects. METHODS–A prospective, single armed, unmasked clinical trial was undertaken at Moorfields Eye Hospital. Twenty consecutive patients with moderate or marked conjunctival inflammation due to OCP were treated with oral sulphapyridine 500 mg twice daily. The degree of ocular inflammation was assessed as nil, mild, moderate, marked, or severe. Success was defined as resolution to mild or less. Ocular limbitis, systemic features of the disease, and side effects of the drug were also monitored. RESULTS–Follow up was a mean of 12.3 (SD 4.0) months and ranged from 7 to 17 months. A successful reduction in inflammation was recorded in 22/39 eyes (56%) and 10/20 patients (50%). This improvement occurred within 1 month in 64% and in all by 2 months. Three patients developed allergy. Other side effects included nausea (n = 3), headache (n = 1), urinary hesitancy (n = 1), and mild lymphocytopenia (n = 1). These were dose dependent. Progression of cicatrisation was observed in 1/22 eyes. Success was less likely if there were systemic features of OCP or ocular limbitis. CONCLUSIONS–Sulphapyridine was clinically effective in 50% of patients with moderate marked inflammation and had few side effects. It is a good alternative to dapsone.